Lipopolysaccharides promote pulmonary fibrosis in silicosis through the aggravation of apoptosis and inflammation in alveolar macrophages - Tan, Shiyi (Open Life Sci, 2020)
Alveolar macrophages (AMs) play an important defensive role by removing dust and bacteria from alveoli. Apoptosis of AMs is associated with lung fibrosis; however, the relationship between this apoptotic event and environmental factors, such as the presence of lipopolysaccharides (LPSs) in the workplace, has not yet been addressed. To investigate whether exposure to LPS can exacerbate fibrosis, we collected AMs from 12 male workers exposed to silica and incubated them in the presence and absence of LPS for 24 h. We show that the levels of cleaved caspase-3 and pro-inflammatory cytokines interleukin (IL)-1β, IL-6, and tumor necrosis factor-alpha were increased in these AMs following LPS treatment. Moreover, we demonstrate that LPS exposure aggravated apoptosis and the release of inflammatory factors in AMs in a mouse model of silicosis, which eventually promoted pulmonary fibrosis. These results suggest that exposure to LPS may accelerate the progression of pulmonary fibrosis in silicosis by increasing apoptosis and inflammation in AMs.